Implementation of a virtual escape room mock code to comply with social distancing. (March 2022) - Lyman, Kerri
Abstract: Background: Despite a global pandemic with social distancing regulations, nurses must continue to participate in continuing education to ensure competency for the care they provide. Mock codes are common yearly competencies that nurses must participate in to grow their critical thinking and show mastery of the skills. Maintaining mock codes which were usually in person, became a struggle in order to comply with social distancing. Method: A virtual escape room mock code was implemented as a substitute for in-person education to sustain continued education during a time of social distancing. The aim was to determine if the virtual sessions met the perceived expectations of the nurses in comparison to previous in-person sessions. The session was designed based upon the Community of Inquiry framework for participants to work together in a meaningful capacity. After completion of the session, a survey which included an adaption of the Student Satisfaction and Self-Confidence in Learning Survey, was disseminated to pediatric and Pediatric Intensive Care Unit (PICU) nurses to gauge their satisfaction and perceptions compared to an in-person method. Results: Results indicated that the nurses felt satisfaction and self-confidence in learning and that virtual session provided equal education as compared to previous in-person sessions. Conclusion: The virtual escape room mock code engaged the nursing staff in an interactive educational opportunity which fulfilled their annual competency requirement.